Minimizing stroke risk in off-pump CABG: the role of clampless devices and the piggyback proximal anastomosis technique - Baudo, Massimo; Cabrucci, Francesco; Yakobitis, Amanda; Murray, Courtney; Torregrossa, Gianluca (Frontiers in Cardiovascular Medicine, 2025)
IntroductionNumerous techniques have been developed to minimize risk of perioperative stroke during coronary artery bypass grafting (CABG), including off-pump approach, preoperative and intraoperative imaging of the ascending aorta (CT scan and epiaortic ultrasound), anaortic CABG with bilateral internal thoracic artery, clampless devices for the construction of proximal anastomosis and minimal aortic manipulation with a single aortic inflow for all proximal grafts (piggyback proximal anastomosis). The aim of this study was to evaluate the clinical outcomes of CABG patients who underwent off pump CABG with proximal anastomosis constructed with the use of a clampless device and in a piggyback fashion.MethodsThis observational study included 112 consecutive patients undergoing CABG with the piggyback proximal technique at the Lankenau Heart Institute between June 2021 and January 2024. Primary endpoints included overall mortality, cardiac-related mortality, stroke, myocardial infarction, repeat revascularization. Intraoperative transit time flow measurement (TTFM) was also analyzed.ResultsThe mean age of the cohort was 67.8 ± 8.7 years, with 75.9% (85/112) being male. All patients underwent off-pump CABG. The piggyback anastomosis consisted of vein-on-vein (52.7%, 59/112), artery-on-vein (43.8%, 49/112), and double vein/artery configurations (3.6%, 4/112). Postoperatively, no strokes occurred. At 30 days no patient died or required repeat revascularization. The mean hospital stay was 5.5 [4.0–8.0] days. At a mean follow-up of 1.0 [0.5–1.7] years, no cardiac deaths were recorded, with an overall survival of 98.2% (110/112). Repeat piggyback revascularization was 3.6% (4/112) at a mean of 2.0 ± 0.5 years. TTFM demonstrated superior flow rates in artery-on-vein grafts [50 (40–70) ml/min] compared to vein-on-vein grafts [40 (30–53.5), p < 0.001].ConclusionsWhen a proximal anastomosis cannot be avoided during off pump CABG, the combination of a piggyback proximal anastomosis together with the use of a clampless aortic device, demonstrated promising early mid-term outcomes almost nullifying the perioperative risk of clinical stroke. Intraoperative TTFM showed excellent flow rates, especially when arterial grafts were used. The technique is a viable option in high-risk patients with severe aortic disease, offering a safe and effective approach to multivessel revascularization with minimal aortic manipulation. Further studies with longer follow-up are warranted to confirm its long-term benefits.